Nuclear-specific accumulation of telomerase reverse transcriptase (TERT) mRNA in TERT promoter mutated follicular thyroid tumours visualised by in situ hybridisation: a possible clinical screening tool?. Issue 10 (19th May 2021) - Hellgren, L Samuel; Olsson, Ann; Kaufeldt, Ann; Paulsson, Johan O; Hysek, Martin; Stenman, Adam; Zedenius, Jan; Larsson, Catharina; Höög, Anders; Juhlin, C Christofer
Abstract : Aims: Upregulation of the telomerase reverse transcriptase ( TERT ) gene is a frequent finding in follicular thyroid carcinomas (FTCs) with metastatic features. The augmented expression is usually caused by TERT promoter mutations. As TERT protein immunohistochemistry might not correlate to TERT mRNA levels in follicular thyroid tumours, we therefore sought to determine if visualisation of TERT mRNA through in situ hybridisation could highlight high-risk cases. Methods: We collected formalin-fixated paraffin-embedded tissues from 26 follicular thyroid tumours; 7 FTCs, 2 follicular thyroid tumours of uncertain malignant potential (FT-UMPs) and a single Hürthle cell carcinoma with established TERT promoter mutations and gene expression, as well as 16 FTCs with no TERT gene aberrancy or gene expression, and assessed them using RNA Scope in situ hybridisation (ISH) and TERT probes targeting the two main TERT transcripts ( TERT1 and TERT2 ). Results: TERT 1 and/or 2 mRNA was found by ISH in 8/10 cases with established promoter mutations and mRNA expression, whereas all 16 cases without TERT gene aberrancies or gene expression were negative (Fisher's exact p<0.001). Strikingly, TERT mRNA was visualised in the nuclear compartment only, thereby corroborating earlier studies suggesting a non-conventional role for TERT in tumour biology. Moreover, TERT mRNA expression was scattered across the tissue sections and only found in a few percentages of tumour nuclei. Conclusions: TERT mRNA seems to be focally expressed and localised exclusively to the nucleus in TERT promoter mutated follicular thyroid tumours, possibly reflecting a true biological and unorthodox phenomenon worthy of further investigations.